Hypoxic stress up-regulates the expression of Toll-like receptor 4 in macrophages via hypoxia-inducible factor - Kim, So Young (Blackwell Science Inc, 2010)
Toll-like receptors (TLRs) are germline-encoded innate immune receptors that recognize invading micro-organisms and induce immune and inflammatory responses. Deregulation of TLRs is known to be closely linked to various immune disorders and inflammatory diseases. Cells at sites of inflammation are exposed to hypoxic stress, which further aggravates inflammatory processes. We have examined if hypoxic stress modulates the TLR activity of macrophages. Hypoxia and CoCl(2) (a hypoxia mimetic) enhanced the expression of TLR4 messenger RNA and protein in macrophages (RAW264.7 cells), whereas the messenger RNA of other TLRs was not increased. To determine the underlying mechanism, we investigated the role of hypoxia-inducible factor 1 (HIF-1) in the regulation of TLR4 expression. Knockdown of HIF-1α expression by small interfering RNA inhibited hypoxia-induced and CoCl(2)-induced TLR4 expression in macrophages, while over-expression of HIF-1α potentiated TLR4 expression. Chromatin immunoprecipitation assays revealed that HIF-1α binds to the TLR4 promoter region under hypoxic conditions. In addition, deletion or mutation of a putative HIF-1-binding motif in the TLR4 promoter greatly attenuated HIF-1α-induced TLR4 promoter reporter expression. Up-regulation of TLR4 expression by hypoxic stress enhanced the response of macrophages to lipopolysaccharide, resulting in increased expression of cyclooxygenase-2, interleukin-6, regulated on activation normal T cell expressed and secreted, and interferon-inducible protein-10. These results demonstrate that TLR4 expression in macrophages is up-regulated via HIF-1 in response to hypoxic stress, suggesting that hypoxic stress at sites of inflammation enhances susceptibility to subsequent infection and inflammatory signals by up-regulating TLR4.